Racionalizace výroby koncovek - Grandič, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Tato práce byla vytvořena ve spolupráci s firmou Westfalia. Cílem této práce je zanalyzovat možnosti racionalizace výroby koncovek plynotěsných hadic používaných v automobilovém průmyslu. Práce obsahuje studii racionalizace možné výroby 2. generace koncovek a také dokončení montážního pracoviště pro současnou generaci výroby koncovek.

This thesis was created in cooperation with company Westfalia. The aim of this work is to analyze the possibility of rationalization of production of end parts for gas tight hoses used in the automotive industry. The thesis includes a study of rationalization of possible production of the second generation of end parts as well as completion of assembly line for the current generation of end parts.
Rationalization of production end piece
Keywords: racionalizace; koncovky GTH; plynotěsné hadice; rationalization; end piece GTH; gas tight hoses